2017
DOI: 10.1038/gt.2017.11
|View full text |Cite
|
Sign up to set email alerts
|

IL-4 mediated by HSV vector suppresses morphine withdrawal response and decreases TNFα, NR2B, and pC/EBPβ in the periaqueductal gray in rats

Abstract: Chronic opiates induce the development of physical dependence. Opioid physical dependence characterized by withdrawal symptoms, may have very long-lasting effects on the motivation for reward, including the incubation of cue-induced drug-seeking behavior. Elucidation of the mechanisms involved in physical dependence is crucial to developing more effective treatment strategies for opioid dependence. Chronic morphine induces production of proinflammatory cytokines in regional-specific sites of the brain. Interle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 72 publications
0
3
0
Order By: Relevance
“…Although the current study focused solely on weight loss, as it is a prominent symptom of rodent opioid withdrawal, it would be interesting to investigate TNF-α’s effect on other withdrawal behaviors such as wet dog shakes, teeth chattering, and diarrhea. It is possible that these behaviors may also be mediated by TNF-α signaling, as it has been previously shown that downregulating TNF-α signaling in the periaqueductal gray (PAG) of mice decreased the physical symptoms of morphine withdrawal [ 63 ]. In particular, studies have shown that heroin administration can directly stimulate glial toll-like receptor 4 (TLR4) that results in the overexpression of TNF-α and injection of TNF-α into the PAG produces withdrawal symptoms [ 64 ].…”
Section: Discussionmentioning
confidence: 99%
“…Although the current study focused solely on weight loss, as it is a prominent symptom of rodent opioid withdrawal, it would be interesting to investigate TNF-α’s effect on other withdrawal behaviors such as wet dog shakes, teeth chattering, and diarrhea. It is possible that these behaviors may also be mediated by TNF-α signaling, as it has been previously shown that downregulating TNF-α signaling in the periaqueductal gray (PAG) of mice decreased the physical symptoms of morphine withdrawal [ 63 ]. In particular, studies have shown that heroin administration can directly stimulate glial toll-like receptor 4 (TLR4) that results in the overexpression of TNF-α and injection of TNF-α into the PAG produces withdrawal symptoms [ 64 ].…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, opioid withdrawal is mediated by the activation of proinflammatory systems in the PAG. Induction of the interleukin-4 gene (Il4) with a recombinant vector blunted the morphine withdrawal syndrome in mice (59). Microinjection of a herpes simplex virus vector in the PAG to decrease tumor necrosis factor a before the start of morphine treatment significantly reduced naloxoneprecipitated withdrawal in mice (60).…”
Section: Between-system Neuroadaptationsmentioning
confidence: 99%
“…We recorded the body weight of each rat before the injection of naloxone and then again at 60 min after naloxone. The scored signs defined in our previous work 24 , were based on our previous experience as modified from those described by Punch et al 13 . A global withdrawal score was calculated for each rat by assigning a combination of the various physical signs of withdrawal 25 .…”
Section: Animal and Evaluation Of Chronic Morphine Physical Dependencementioning
confidence: 99%